Detection of rabies virus in insectivorous bats from the urban area in Monterrey Nuevo Leon, Mexico - Reyna, E. J.; Pérez, J. Z. V.; Galindo, E. I. G.; Rosales, P. C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
In Mexico there are 154 species of bats, of these, 37 are distributed in Nuevo Leon, which can be insectivorous, frugivorous, or hematophagous. The most common bat in Nuevo Leon is Tadarida brasiliensis mexicana, it is and insectivorous, and it is also the smallest free-tailed bats. There are other species of insectivorous bats, such as Nycticeius humeralis, Myotis sp, Lasiurus ega, Eumops perotis, Antrozous pallidus, Corynorhinus townsendii, Lasiurus cinereus, and Leptonycteris nivalis, which are useful in maintaining ecological balance, contributes to the spread of seeds, and eat insects that harm agriculture. However, in 1984 the rabies virus was reported in Tadarida brasiliensis mexicana , and in 1998 the first human death caused by rabies transmitted by bats insectivorous was reported in Latin America. Between 2009 and 2010, 7 cases of the variant V-9 were diagnosed and they corresponded to the same domestic species, Canis familiaris and Felis catus. In rural areas of Nuevo Leon, as well as in the urban area of Monterrey there are habitats for different species of bats. Monterrey is the capital of the state and the third most populous city in Mexico, there, the highest number of cases have been detected. Therefore, the objective of this study was to detect cases of rabies in the urban area of Monterrey because of potential risk for humans and domestic animals. During 2011 and 2012, 21 bat samples were analyzed by using immunofluorescence, antigenic characterization and genotyping techniques,. Identification of species showed 14 Tadarida brasiliensis, 3 Lasiurus sp, 1 Nycticeius humeralis, 1 Leptonycteris nivalis, 1 Lasiurus ega, and 1 Lasiurus cinereus. From these, 8 bats were positive for rabies virus, and an antigenic characterization was performed using 8 monoclonal antibodies, with this study, the variant 9 (V-9) was the most predominate. Genotyping of Lasiurus ega and Lasiurus cinereusse samples showed 99% of similitude with Lasiurus intermedius. This study demonstrates the high prevalence of rabies in insectivorous bats, which threatens both humans and domestic animals, and suggests the implementation of sustainable programs to prevent cases of rabies in these species. Acknowledgements: We are grateful to Miguel Angel Zuniga, Isabel Aguilar Tavitas and Alma Liliana Lizarán Meneses for their support in the diagnosis of rabies virus.